PERBANDINGAN VEGETASI TUMBUHAN BAWAH DI BAWAH EMPAT JENIS TEGAKAN HUTAN TANAMAN DI CANDIKUNING, BALI - SIREGAR, MUSTAID (Research Center for Biology-Indonesian Institute of Sciences, 1987)
MUSTAID SIREGAR. 1987.The comparison of ground vegetation under four forest plantations in Candikuning, Bali. Suppl. BeritaBiologi. 3: 45-50.The ground vegetation under four forest plantations of different species in Candikuning (Altingia excelsa, Manglietia glauca, Agathis dammara, Pinus merkusiij have been investigated by using quadrat method. The results showed that the highest index of similarity was 53,06% between A. dammara and P. merkusii plantations, and the lowest index of similarity was 18,21% between A. excelsa and P. merkusii plantations. The species composition and community stability of these ground vegetations under